Post-Discharge Experiences of People with Psychosis Following Partial Hospital Program Completion. (3rd July 2018) - Roby, Rachel C. L.; Shapira Goldstein, Rebecca L.; Rose, Ebony St.; Kerman, Nick
ABSTRACT: Partial hospital programs are day programs which act as a bridge between inpatient and outpatient care for people with severe and persistent mental illness. This study explored the gap that exists in understanding the post-discharge experiences of people who have experienced psychosis. Qualitative interviews were conducted with 8 participants with psychosis, at least 4 weeks after completing partial hospital program. Identified themes included improved sense of wellness, changes in structure/routine, accessing community resources, social support and engagement, engagement in leisure, and impact of medication. Occupational therapists can use these findings to enhance programming at partial hospital programs and other similar programs.